Targeting the IRE1-XBP1 axis to overcome endocrine resistance in breast cancer: Opportunities and challenges. (28th August 2020) - Barua, David; Gupta, Ananya; Gupta, Sanjeev
Abstract: Estrogen receptor 1 (ESR1, which encodes estrogen receptor-alpha) is a key driver gene for the initiation and progression of hormone receptor-positive breast cancer. Estrogen receptor-alpha (ER) is expressed in up to 70% of cases, and patients are routinely treated with endocrine therapies. However, the development of resistance over time is common and occurs in one-third of ER-positive breast tumors, leading to disease progression and death. X-box binding protein 1 (XBP1), a key component of the unfolded protein response (UPR) and ER signaling pathway, generates a positive feedback regulatory loop that leads to increased expression of XBP1 and ER in luminal breast cancer. In this review, we highlight new insights into the mechanisms of crosstalk between XBP1 and ER signaling and its clinical implications. Next, we describe the key signaling nodes that play an important role in XBP1-mediated endocrine resistance in breast cancer. Further, we discuss XBP1 gene mutations in breast cancer and the role of these mutations in the emergence of endocrine resistance and response to treatment. Finally, we discuss the current state and future directions for targeting XBP1 in combination with standard endocrine therapy to improve clinical outcomes in endocrine-resistant breast cancer patients. Highlights: Crosstalk between estrogen signaling pathway and IRE1-XBP1 axis generates a positive feed forward loop in breast cancer. XBP1 expression is elevated in endocrine resistant breast cancers. Co-targeting of XBP1 in combination with anti-estrogen therapy is a novel approach to overcome endocrine resistance in breast cancer. Due to undesired side effects of IRE1 inhibitors there is urgent need to develop new strategies to directly target XBP1.